Family-focused obesity prevention program implementation in urban versus rural communities: a case study - Colleen Flattum; Sarah Friend; Melissa Horning; Rebecca Lindberg; Jennifer Beaudette; Jayne A. Fulkerson (BMC, 2021)
Abstract Purpose Despite public health efforts to reduce childhood obesity, there remains an unequal distribution of obesity among rural and urban children, with higher rates in rural areas. However, few studies have compared differences in program delivery. This paper aims to describe differences between an urban and rural program delivery of a family-focused, community-based intervention program to prevent and reduce obesity among children. Methods This paper uses a case study format to provide a descriptive analysis of similar obesity prevention programs, designed by the same research team, implemented in Minnesota in different settings (i.e., an urban and rural setting) with significant community engagement in the adaptation process. The rural NU-HOME program is compared to HOME-Plus, an urban family-based obesity prevention program for school-aged children. Results Community engagement in the adaptation process of an urban program to a rural program confirmed some anticipated program content and delivery similarities while identifying key differences that were necessary for adaptation related to engagement with the community, recruitment and data collection, and intervention delivery. Discussion When adapting research-tested programs from urban to rural areas, it is important to identify the modifiable behavioral, social, and environmental factors associated with obesity to ensure the content of effective childhood obesity prevention programs is relevant. Customizing a program to meet the needs of the community may increase reach, engagement, and sustainability. In addition, long-term dissemination of a tailored program may significantly reduce childhood obesity in rural communities and be implemented in other rural settings nationally.